Boundary layer flow and heat transfer of a micropolar fluid near the stagnation point on a stretching vertical surface with prescribed skin friction - Ahmad, Kartini; Nazar, Roslinda; Pop, Loan (Beijing Keji Daxue, 2011)
The steady laminar mixed convection boundary layer flow and heat transfer of a micropolar fluid near the stagnation point on a stretched vertical surface with prescribed skin friction were considered. The governing partial differential equations were transformed into a system of ordinary differential equations, which were then solved numerically using the shooting method. Results for the stretching velocity, the local Nusselt number, the temperature, and the velocity profiles are presented for various values of the mixed convection parameter λ and material parameter K when the Prandtl number is equal to 1. Both assisting (heated plate) and opposing (cooled plate) flow regions are considered. It is found that dual solutions exist for both assisting and opposing flows.